2019
DOI: 10.7759/cureus.5502
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Comorbidities in Hospitalizations for Cannabis Use-associated Intractable Vomiting during Post-legalization Period

Abstract: The aim of this study was to observe the trends of intractable vomiting and cannabis use disorder (CUD) with demographic characteristics, medical and psychiatric comorbidities, and hospitalization outcomes. Methods We conducted a retrospective cohort study using the nationwide inpatient sample (2010 to 2014). Patients aged 16-50 years discharged with a primary diagnosis of intractable vomiting and CUD were included (N = 9,601). We used the linear-by-linear association chi-square test and independent-sample T-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A large case series suggested that sufferers are typically under 50 years old, may experience weight loss with the onset of the disorder, have morning predominance of symptoms, have normal bowel habits and negative investigations 33 . Anxiety and depression appear to commonly coexist in CHS sufferers 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large case series suggested that sufferers are typically under 50 years old, may experience weight loss with the onset of the disorder, have morning predominance of symptoms, have normal bowel habits and negative investigations 33 . Anxiety and depression appear to commonly coexist in CHS sufferers 34 …”
Section: Discussionmentioning
confidence: 99%
“…33 Anxiety and depression appear to commonly coexist in CHS sufferers. 34 The Rome IV criteria are the first attempt to characterise CHS by the Rome group in 2016. Unfortunately, the requirement for re- The same authors also showed significant overlap with CVS, with a reasonable assertion that CHS could be a subset of CVS with the added component of cannabis use.…”
Section: First Described In 2004 By Allen Et Al Chs Is Characterised Bymentioning
confidence: 99%
“…24 The hospitalization rates for cannabisassociated intractable vomiting had increased by 28.6% from 2010 to 2015. 25 One pattern in CHS is recreational marijuana use, often starting during high school or college and continuing on a daily basis. The symptoms of cyclic vomiting episodes usually start after chronic daily intake for approximately 5 years.…”
Section: Epidemiologymentioning
confidence: 99%
“…These advances enhanced the understanding of cannabinoid (CB) receptors, which led to a better appreciation of the role of cannabis in inflammation, seizures, emesis, and as an appetite stimulant. There is a growing body of research showing the benefit of cannabis in the aforementioned disorders, and its legalization will further augment research on understanding its critical role in new drug developments [ 3 , 4 ]. However, these changes also come with substantial risks regarding its adverse effects, such as paradoxical hyperemesis, intoxication and behavioral changes (anxiety, panic attacks, and psychoactive changes).…”
Section: Introductionmentioning
confidence: 99%